Antecedents of entrepreneurial processes of effectuation and opportunity creation - Adamu, Ado Makama; Raja Yusof, Raja Nerina; Sambasivan, Murali (Human Resource Management Academic Research Society, 2022)
Extant literature of Entrepreneurial opportunity studies has identified two opposing theoretical viewpoints. Theory of opportunity discovery known as “causation” is the initial perspective. The second perspective is opportunity creation. The legitimacy of opportunity discovery theory in studying entrepreneurship is challenged by scholars. Among many developing theoretical perspectives, Sarasvathy's (2001) effectuation theory is extensively cited in entrepreneurial literature. Due to the novelty of effectuation theory, previous studies of opportunity creation are conceptual in nature or qualitative, and at best experimental; the antecedents of effectuation theory are unexplored. A questionnaire was created and distributed to 1,950 in Nigeria. The objectives of this study are (i) to discover factors that can predict entrepreneurs’ effectual behaviours, (ii) to observe the effect of entrepreneurial effectuation on opportunity creation process and (iii) to explore how venture performance is affected by entrepreneurial opportunity creation. Findings of this study established that entrepreneur’s management skill and entrepreneurs’ personality traits characteristics are significant to entrepreneurial process effectuation. Also entrepreneurial process of effectuation is a significant predictor of entrepreneurial opportunity creation.